An Overview of Post-Traumatic Stress Disorder (PTSD) Among Flash Flood Victims - Cipto Cipto; Siswoko Siswoko; Muawanah Muawanah; Ajeng Titah Normawati (Journal of Applied Health Management and Technology, 2023)
Flash flood disaster is a natural disaster that can have a negative impact on victims. The psychological impact caused after the disaster is in the form of Post-Traumatic Stress Disorder (PTSD) which shows several symptoms in the form of Re-experiencing, Avoidance, and Hyper arousal. This research was conducted with the aim of knowing the description of Post-Traumatic Stress Disorder (PTSD) in the victims of the flash flood disaster one year after the incident. The method used in this study is descriptive research with a survey approach. The sample technique used in this study is a purposive technique. Data analysis used univariate analysis to determine the characteristics of the respondents which included age, occupation, gender, education, and description of PTSD symptoms. This study involved 48 people as respondents who showed the characteristics of 70% meeting the PTSD diagnostic criteria after the flash flood that hit their village two years ago. The results of this study can be used as a reference or basis for preparing interventions to improve mental health in communities especially those experiencing disasters.